PEMBARUAN HUKUM KELUARGA ISLAM: Studi Kasus Hukum Waris di Somalia - Ahmad Syafi'i (Al-Syakhsiyyah: Journal of Law & Family Studies, 2021)
Abstract: This article aims to examine one of the phenomena that emerged in the Muslim world in the 20th century, namely the renewal of family law in Muslim-majority countries. This article focuses on the study of inheritance law reform in Somalia. By using a legal political approach, this article examines several important issues, i.e.,: the model of inheritance law reform in Somalia, the reasons that led to the revolutionary change from the concept of Islamic inheritance in general, and and the factors that influence these changes. In general, this study shows that in the reform of family law in Somalia, there are several rules that are not much different from the concept of the imam of the school of thought, but there are also several legal rules that are quite far from the conceot of conventional, especially the legal rules related to inheritance.